PEMBUATAN APLIKASI PADA PRAKTIK MANDIRI BIDAN MENGGUNAKAN METODE WATERFALL - Andri Permana Wicaksono; Dara Ayu Sadiyanti Rukmana; Mudafiq Riyan Pratama (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
Patient medical record in Midwife Independent Practice (MIP) must save and keep the secret for give quality of health care, quantity, and quick response to patients. MIP of Erliyanti Sukirno, S.ST,. Tanah Bumbu build at 2012. Since 11 years old, patients must queue in waiting room in quite a while. This is because of the service process and medical record using manual. The purpose of this research is to make a design for MIP application. Researchers use the research and development method to facilitate the research process and the waterfall method as a reference for the MIP application development process. The product is MIP application can give ease to the midwife officer in providing service to the patient and reduce the length of the patient queue in waiting room. Data collection used interview to 2 respondents are the owner of MIP and midwife. The result is functional system needs and non-functional to MIP application. Then, needed to transmit in system design by flowchart system, use case diagram, class diagram, activity diagram, entity relationship diagram, and data flow diagram. The design is then translated to a programming language using PHP program and MySQL database. From the results of this study, it has several features are login features, patient visit report features, patient referral letter features, patient and midwife detail identity data features, notification features, patient registration features independently, and feature records of patient examination results. Features that unavailable in the MIP application are the automatic payment features and the distance between the MIP and the referred hospital.